Development of android based learning media on the subjects of digital photo composition for vocational high school student - Rini Sefriani; Indra Wijaya; Popi Radyuli (Department of Electrical Engineering Education, Faculty of Teacher Training and Education, 2018)
This study aims to develop an Android SmartPhone based learning media for Digital Photo Composition in Vocational High School. This research is a Research and Development, conducted in Vocational Secondary School class XI. The results of the assessment of the three validators overall validator test assessment of the Interactive Module of 88.00% so that the level of validity can be interpreted very Valid is used. Overall assessment of the practicality of learning media based SmartPhone Andorid as learning resources of 83.96%, so that practical level can be interpreted Practically used. And assessment of the effectiveness of learning media based Andorid SmartPhone as learning resources of 89.19%, so the level of effectiveness can be interpreted Very Effective use.